RESULT QUALITY ASSESSMENT OF SHEEP SKIN GOLF GLOVES TANNING BASED ON THERMAL AND MICROBIAL RESISTANCE - Chorynur Retmaningrum; Mustafidah Udkhiyati; Elis Nurbalia (Politek ATK Yogyakarta Press, 2024)
The limited availability of domestic raw materials has encouraged the leather tanning industry to import raw materials from various countries. The condition of skin raw materials imported from abroad is generally in the form of pickle or wet blue-like (skin that has been chrome tanned in small amounts (1.5% (w/w)). Industry concerns regarding the adequacy of tanning degree on wet blue-like skin conducing the treatment being carried out using the same method and amount of tanning agent for both pickle and wet blue-like skin. Thus, potentially causing excessive use of chrome. This research compares the effect of tanning treatment on thermal and microbial resistance as well as physical characteristics of glove leather with wet blue-like skin raw materials. Based on the research results, it is known that treatment without re-chroming produces lower thermal and microbial resistance than treatment with re-chroming. However, the formulation without re-chroming treatment on wet blue-like skin can be recommended for application considering that the results obtained have characteristics in accordance with the requirements according to SNI 06-0777-1996. The application without re-chroming formulations can enable produce efficiency due to the use of less chrome and faster operational times. Still, adjustments need to be made regarding handling to prevent the growth of microorganisms. This is because the probability of growth of microorganisms when applying formulations without tanning is higher than formulations with tanning.